6-2(2w-1)=9w-2(9+w)

Simple and best practice solution for 6-2(2w-1)=9w-2(9+w) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(2w-1)=9w-2(9+w) equation:


Simplifying
6 + -2(2w + -1) = 9w + -2(9 + w)

Reorder the terms:
6 + -2(-1 + 2w) = 9w + -2(9 + w)
6 + (-1 * -2 + 2w * -2) = 9w + -2(9 + w)
6 + (2 + -4w) = 9w + -2(9 + w)

Combine like terms: 6 + 2 = 8
8 + -4w = 9w + -2(9 + w)
8 + -4w = 9w + (9 * -2 + w * -2)
8 + -4w = 9w + (-18 + -2w)

Reorder the terms:
8 + -4w = -18 + 9w + -2w

Combine like terms: 9w + -2w = 7w
8 + -4w = -18 + 7w

Solving
8 + -4w = -18 + 7w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-7w' to each side of the equation.
8 + -4w + -7w = -18 + 7w + -7w

Combine like terms: -4w + -7w = -11w
8 + -11w = -18 + 7w + -7w

Combine like terms: 7w + -7w = 0
8 + -11w = -18 + 0
8 + -11w = -18

Add '-8' to each side of the equation.
8 + -8 + -11w = -18 + -8

Combine like terms: 8 + -8 = 0
0 + -11w = -18 + -8
-11w = -18 + -8

Combine like terms: -18 + -8 = -26
-11w = -26

Divide each side by '-11'.
w = 2.363636364

Simplifying
w = 2.363636364

See similar equations:

| 24=-6+3y | | 9q=-36 | | 1.8(a-1)=-0.7(a-11) | | -3x+8y=-19 | | -16-4+4p+6p=2p+4 | | 4(6x+3)+9=12 | | 3x+3=-2+2+6 | | 2x-4x+5x-6x= | | -5x+9y=-23 | | 12-(3m+5)=2+2-15 | | -9q=-144 | | 6x-2=-7 | | 4x-9x+8x-6x= | | 6=t-2 | | 4y-2(y-1)+4= | | 3(5+9*7)=3(5+9*7) | | -7x+6=-6x-2x | | 3x+6=8+2x-6 | | 0.17(z+0.2)=-0.8(z+0.125) | | 6y-4(y-2)+6= | | x^4-64x^2=0 | | 4(x-8)-8x= | | 5n-4n=-5+2n | | 32-4(2w+1)=8w-4(8+w) | | -4v-8-2v=8v | | 20d^2+27d+9=0 | | -69=-30 | | X(3x+4y-13)= | | x=5x-28 | | p/6=0 | | -9x+6x-7x=0 | | -0.17(z-0.2)=-0.5(z+2) |

Equations solver categories